Low-Order Damping and Tracking Control for Scanning Probe Systems - Fleming, Andrew J.; Teo, Yik Ren; Leang, Kam K. (Frontiers in Mechanical Engineering, 2015)
This article describes an improvement to integral resonance damping control (IRC) for reference tracking applications such as Scanning Probe Microscopy and nanofabrication. It is demonstrated that IRC control introduces a low-frequency pole into the tracking loop which is detrimental for performance. In this work, the location of this pole is found analytically using Cardano's method then compensated by parameterizing the tracking controller accordingly. This approach maximizes the closed-loop bandwidth whilst being robust to changes in the resonance frequencies. The refined IRC controller is comprehensively compared to other low-order methods in a practical environment.